Solid oxide electrolytic cell capable of self-enriching carbon dioxide and preparation method of solid oxide electrolytic cell
By using nanocatalysts and composite ceramic materials in solid oxide electrolytic batteries, self-enrichment of fossil fuels efficiently converted into hydrogen and carbon dioxide is achieved, solving the problems of low hydrogen production efficiency and high carbon dioxide capture cost in the prior art, and reducing hydrogen production power consumption and capture cost.
Patent Information
- Application Number
- CN202411770150.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, the hydrogen production efficiency of fossil fuel reforming is low, the electricity consumption of hydrogen production by electrolyzing water is high, and the carbon dioxide capture cost is high, making it difficult to achieve efficient hydrogen production and self-enrichment of carbon dioxide.
A solid oxide electrolytic battery that is self-enriched with carbon dioxide is used to generate hydrogen by passing water vapor or hydrogen mixture to the negative electrode to produce hydrogen; a combustible gas is used to carry out deep or complete oxidation reaction to produce carbon dioxide. The negative and positive electrodes of the battery are both covered with nanocatalysts to improve the reaction efficiency.
The efficient conversion of fossil fuels into hydrogen is achieved, which reduces the power consumption of hydrogen production, improves the production efficiency of hydrogen, and reduces its capture cost through self-enrichment of carbon dioxide.
Smart Images

Figure CN119663311A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electrolytic cell and a preparation method thereof, in particular to a solid oxide electrolytic cell capable of self-enriching carbon dioxide and a preparation method thereof. Background Art
[0002] Hydrogen energy is a secondary energy source that is abundant in source, green, low-carbon and widely used. It is gradually becoming one of the important carriers of global energy transformation and development. At present, most of the hydrogen demand is met by producing hydrogen from fossil fuels, that is, through steam reforming of natural gas and coal gasification. However, traditional fossil fuel hydrogen production will produce high carbon dioxide emissions, and the cost of capturing carbon dioxide is very high. The process of hydrogen production by water electrolysis has no carbon dioxide emissions and is an important source of hydrogen in the future. However, the current electricity consumption of hydrogen production by water electrolysis is too high, and the high electricity cost has become an important barrier to the rapid large-scale promotion and application of hydrogen production by water electrolysis.
[0003] In the prior art, US6051125 couples natural gas into a high-temperature electrolyzer, but CO is very likely to undergo a disproportionation reaction in a Ni metal ceramic catalyst at high temperature, resulting in carbon deposition. On the other hand, the Ni in the Ni metal ceramic catalyst is easily oxidized in an oxidizing atmosphere, resulting in failure. The Chinese patent with publication number CN101103140A uses metal Ni in the anode, and methane is easily cracked and carbonized under the action of Ni at high temperature, covering the electrode and causing electrode blockage. In order to prevent carbon deposition, water vapor or carbon dioxide needs to be mixed into methane during operation, which makes the operation of the electrolytic cell more complicated.
[0004] In general, the steam reforming reaction currently occurs in fossil fuel reforming hydrogen production, which is a strong endothermic reaction. Therefore, in the traditional hydrogen production process, a part of the fossil fuel needs to be burned to maintain the continuous reforming reaction in the thermochemical reactor. Therefore, the hydrogen production efficiency in the traditional hydrogen production process is low (taking natural gas reforming hydrogen production as an example, one standard cubic meter of natural gas only produces 2.2-2.4 standard cubic meters of hydrogen). At the same time, in the process of capturing carbon dioxide, the concentration of carbon dioxide produced by fossil fuel combustion is low, which makes capture extremely difficult and consumes a lot of energy. In traditional water electrolysis hydrogen production, the water electrolysis reaction is also a strong endothermic reaction. The energy of the entire reaction is completely provided by electricity, so the electricity consumption is very large (3-5kWh per standard cubic meter of hydrogen), and the cost of hydrogen production is relatively high. Summary of the invention
[0005] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a solid oxide electrolysis cell for self-enriching carbon dioxide with high hydrogen production efficiency and reduced energy consumption for hydrogen production. Another purpose of the present invention is to provide a method for preparing a convenient and controllable solid oxide electrolysis cell for self-enriching carbon dioxide.
[0006] Technical solution: The solid oxide electrolytic cell for self-enrichment of carbon dioxide described in the present invention comprises a negative electrode current collecting layer, on the surface of which a negative electrode active layer, an electrolyte membrane and a positive electrode active layer are sequentially arranged; the negative electrode current collecting layer is one or more of an electronic conductive phase and an ion conductive phase; the negative electrode active layer and the positive electrode active layer are composite ceramics composed of an electronic conductive phase and an ion conductive phase, and the volume fraction of the electronic conductive phase is not less than 40%; the porosity of the negative electrode current collecting layer is 10-70%, the porosity of the negative electrode active layer is 20-35%, and the porosity of the positive electrode active layer is 20-35%.
[0007] A solid oxide electrolysis cell for self-enrichment of carbon dioxide, wherein water vapor or a water vapor-hydrogen mixture mainly composed of water vapor is introduced into the negative electrode of the cell, and an electrolytic reduction reaction of the water vapor occurs to obtain hydrogen or a hydrogen-water vapor mixture mainly composed of hydrogen; a combustible gas or a mixed gas containing combustible gas is introduced into the positive electrode of the cell, and a deep or complete oxidation reaction of the combustible gas occurs to obtain carbon dioxide or a mixed gas containing a high concentration of carbon dioxide; the combustible gas includes but is not limited to hydrogen, carbon monoxide, methane, ethane, propane, gasoline, diesel, kerosene, methanol, ethanol and a mixed gas thereof.
[0008] Furthermore, the electronic conductive phases in the negative electrode current collecting layer and the negative electrode active layer are Ni, Fe, Cu, Co, FeNi3, 430L, SUS445, SUS446, (La 1-x Sr x )(Cr 1-y Fe y ) 3-δ , (La 1-x Sr x )(Cr 1-y Mn y ) 3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y-z Ni y Mo z O 6-δ One or more of the following, wherein 0<x<1, 0<y<1, 0<δ<1; the ion conductive phase in the negative electrode current collecting layer and the negative electrode active layer is one or more of doped zirconium oxide, doped cerium oxide, doped lanthanum gallate, doped barium zirconate, and doped barium ceria.
[0009] Furthermore, the electronic conductive phase in the positive electrode active layer is 430L, SUS445, SUS446, NiO, CuO, Fe3O4, Co3O4, (La 1-x Sr x)(Cr 1-y Fe y ) 3-δ , (La 1-x Sr x )(Cr 1-y Mn y ) 3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y- z Ni y Mo z O 6-δ One or more of the following, wherein 0<x<1, 0<y<1, 0<δ<1; the ion conductive phase in the positive electrode active layer is one or more of doped zirconium oxide, doped cerium oxide, doped lanthanum gallate, doped barium zirconate, and doped barium ceria.
[0010] In order to accelerate the electrolysis of water and the oxidation reaction of hydrocarbon fuels, the inner surfaces of the negative electrode current collecting layer and the negative electrode active layer are covered with nano-negative electrode catalysts with a particle size of 1 to 500 nm. The nano-negative electrode catalysts are Fe, Ni, Cu, Co, FeNi3, Ce 1-x La x O 2-δ 、Ce 1- x Y x O 2-δ 、Ce 1-x Sm x O 2-δ 、Ce 1-x G x O 2-δ 、Ce 1-x Pr x O 2-δ 、Ce 1-x Nd x O 2-δ 、Ce 1-x Ca x O 2-δ 、Ce 1-x Mg x O 2-δ , (La 1- x Sr x )(Cr 1-y Fe y ) 3-δ , (La 1-x Sr x )(Cr 1-y Mn y )3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y-z Ni y Mo z O 6-δ One or more of, wherein 0<x<1, 0<δ<1. Preferably, the nano cathode catalyst is NiO-Ce 0.9 G 0.1 O 2-δ Nanocatalysts. Nanocatalysts can reduce reaction overpotential and improve efficiency.
[0011] Preferably, the thickness of the electrolyte separator is 5 to 10 micrometers, the porosity of the negative electrode current collector layer is 30 to 45%, and the thickness is 50 to 2000 micrometers.
[0012] The negative electrode active layer is the area of water electrolysis reaction. The water electrolysis reaction occurs at the interface of oxygen ion conductive phase, electronic conductive phase and gas phase. Therefore, it is necessary to have two types of oxygen ion conductive phase and electronic conductive phase and form a percolation network with each other. The gas phase is formed by a porous structure. The lower or higher the porosity and thickness, the lower the number of reaction sites. The negative electrode active layer has the largest number of reaction sites in the porosity range of 20-35% and 5-20 microns.
[0013] The electrolyte membrane provides a channel for oxygen ion transmission, so it must be an oxygen ion conductive phase. The thickness of the electrolyte membrane is related to the oxygen ion transmission resistance. The thicker the thickness, the greater the resistance to oxygen ion transmission, and the greater the reflected ohmic impedance. The thinner the thickness, the greater the difficulty in preparation. The range of 5 to 300 microns can ensure both the preparation qualification rate and low oxygen ion transmission resistance.
[0014] The positive electrode active layer is mainly the area where the oxidation reaction of hydrocarbon fuel occurs. The reaction occurs at the interface of oxygen ion conductive phase, electronic conductive phase and gas phase. Therefore, the material needs to have both oxygen ion conductive phase and electronic conductive phase and form a percolation network with each other. The gas phase is formed by a porous structure. The lower or higher the porosity and thickness, the lower the number of reaction sites. The selected porosity range of 20-35% and 5-20 microns has the largest number of reaction sites. The atmosphere of the positive electrode active layer before the reaction is a reducing atmosphere for hydrocarbon fuel, and the atmosphere after the reaction is an oxidizing atmosphere for water vapor and carbon dioxide. Therefore, the material of the positive electrode active layer needs to be able to stably exist under oxidizing and reducing conditions. This setting can achieve 100% conversion of hydrocarbon fuel.
[0015] Furthermore, a positive electrode current collecting layer is also arranged on the surface of the positive electrode active layer, and the positive electrode current collecting layer is one or more of an electronic conductive phase and an ion conductive phase.
[0016] Furthermore, the electronic conductive phase in the positive electrode current collecting layer is 430L, SUS445, SUS446, (La 1-x Sr x )(Cr 1- y Fe y ) 3-δ , (La 1-x Sr x )(Cr 1-y Mn y ) 3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y-z Ni y Mo z O 6-δ One or more of the following, 0<x<1, 0<y<1, 0<δ<1.
[0017] Furthermore, the ion conductive phase in the positive electrode current collecting layer is one or more of doped zirconium oxide, doped cerium oxide, and doped lanthanum gallate, and its porosity is 10 to 70%.
[0018] In order to accelerate the electrolysis of water and the oxidation reaction of hydrocarbon fuels, the inner surface of the positive current collecting layer and the positive active layer is covered with nano-positive electrode catalysts with a particle size of 1 to 500 nm. The nano-positive electrode catalyst is Ce 1-x La x O 2-δ 、Ce 1-x Y x O 2-δ 、Ce 1-x Sm x O 2-δ 、Ce 1- x G x O 2-δ 、Ce 1-x Pr x O 2-δ 、Ce 1-x Nd x O 2-δ 、Ce 1-x Ca x O 2-δ 、Ce 1-x Mg x O 2-δ One or more of, wherein 0<x<1, 0<δ<1. Preferably, the nano cathode catalyst is Ce 0.9 G 0.1 O2-δ Catalysts. Nanocatalysts can reduce reaction overpotential and improve efficiency.
[0019] Furthermore, the thickness of the negative electrode current collecting layer is 50-2000 microns, the thickness of the negative electrode active layer is 5-20 microns, the thickness of the electrolyte separator is 1-1000 microns, the thickness of the positive electrode active layer is 5-20 microns, and the thickness of the positive electrode current collecting layer is 50-2000 microns.
[0020] Efficient hydrogen production by coupling carbon-hydrogen fuel with water electrolysis is achieved through the synergy of positive and negative electrode nanocatalysts and positive and negative electrode active layer materials and microstructures.
[0021] The method for preparing the solid oxide electrolytic cell for self-enriching carbon dioxide comprises the following steps:
[0022] Step 1, preparing a negative electrode current collecting layer green body, a negative electrode active layer green body, an electrolyte separator green body, a positive electrode active layer green body and a positive electrode current collecting layer green body on a Mylar film respectively;
[0023] Step 2, stacking the negative electrode current collector green sheet, the negative electrode active layer green sheet, the electrolyte separator green sheet, the positive electrode active layer green sheet and the positive electrode current collector green sheet, and statically pressing the whole to obtain a solid oxide electrolytic cell green sheet;
[0024] Step three, gradient sintering the product obtained in step two to make the electrolyte membrane layer dense, cooling, and obtaining a solid oxide electrolysis cell that self-enriches carbon dioxide.
[0025] The working principle of the solid oxide electrolysis cell: a mixture of hydrogen and water vapor is introduced at the negative electrode, and a hydrocarbon fuel is introduced at the positive electrode; the water vapor dissociates at the negative electrode to generate hydrogen and oxygen ions, and the oxygen ions are transmitted to the positive electrode through the electrolyte diaphragm to undergo a complete oxidation reaction with the hydrocarbon fuel to generate water and carbon dioxide; the gas at the negative electrode outlet is hydrogen and water vapor, and high-purity hydrogen is obtained after condensation, and the gas at the positive electrode outlet is carbon dioxide and water vapor, and high-purity carbon dioxide is obtained after condensation, which can be directly captured. Coupling fossil fuels into the process of hydrogen production by electrolysis of water releases the energy contained in the fossil fuels in an electrochemical form to compensate for the energy required for electrolysis of water, reduce the power consumption of hydrogen production, and at the same time improve the efficiency of hydrogen production from fossil fuels, and realize self-enrichment of carbon dioxide to facilitate capture. In terms of material selection, carbon deposition-resistant electrode materials are selected to simplify the actual operating conditions and reduce the energy consumption of hydrogen production.
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0027] 1. It can efficiently convert fossil fuels into hydrogen. Taking natural gas as an example, one cubic meter of natural gas can produce four cubic meters of hydrogen. At the same time, it can self-enrich carbon dioxide for easy capture, thus reducing the cost of CCUS in traditional fossil fuel hydrogen production;
[0028] 2. Compared with traditional hydrogen production by water electrolysis, it can greatly reduce the power consumption of hydrogen production (1kWh per standard cubic meter of hydrogen), thereby reducing the cost of clean hydrogen;
[0029] 3. Loading nanocatalysts on the positive and negative electrodes respectively can accelerate the electrolysis of water and the oxidation reaction of hydrocarbon fuels, reduce the reaction overpotential and improve efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a schematic structural diagram of Embodiment 1 of the present invention;
[0031] Figure 2 is a cross-sectional view of embodiment 1 of the present invention;
[0032] Figure 3 is a schematic structural diagram of Embodiment 2 of the present invention;
[0033] Figure 4 is a cross-sectional view of embodiment 2 of the present invention;
[0034] Figure 5 It is a schematic diagram of the operation of the solid oxide electrolysis cell for self-enrichment of carbon dioxide of the present invention;
[0035] Figure 6 is a bar chart of the anode product gas composition of the solid oxide electrolytic cell obtained in Example 4 of the present invention at different currents (dry);
[0036] Figure 7 This is the electrolysis and power consumption curve of the solid oxide electrolysis cell obtained in Example 4 of the present invention. DETAILED DESCRIPTION
[0037] The materials, reagents, instruments, etc. used in the following examples, unless otherwise specified, can be obtained from commercial sources. The experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer. In the following examples, 0<δ<1, and the binder and plasticizer are both polyvinyl butyral.
[0038] Example 1
[0039] A method for preparing a solid oxide electrolytic cell for self-enrichment of carbon dioxide comprises the following steps:
[0040] (1) Preparation of negative electrode current collector green body: NiO, Zr 0.97 Y 0.06 O 2-δand graphite powder in a ratio of 48:32:20, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add polyvinyl butyral as a binder and plasticizer after ball milling, and ball mill again to obtain a uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast and dried on a mylar film to obtain a negative electrode current collector green body.
[0041] (2) Preparation of negative electrode active layer green body: NiO, Zr 0.97 Y 0.06 O 2-δ and graphite powder in a ratio of 54:36:10, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add polyvinyl butyral as a binder and plasticizer after ball milling, and ball mill again to obtain a uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a mylar film and dried to obtain a negative electrode active layer green body.
[0042] (3) Preparation of electrolyte membrane green body: 0.97 Y 0.06 O 2-δ A two-component solvent of xylene and butyl acetate and an acrylic resin dispersant are added to the powder, polyvinyl butyral is added as a binder and a plasticizer after ball milling, and ball milling is performed again to obtain a uniformly dispersed casting slurry; the slurry is filtered and degassed, and then cast and dried on a Mylar film to obtain an electrolyte diaphragm green body.
[0043] (4) Preparation of positive electrode active layer green body: 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ 、Zr 0.97 Y 0.06 O 2-δ and graphite powder in a ratio of 54:36:10, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add polyvinyl butyral as a binder and plasticizer after ball milling, and ball mill again to obtain a uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a mylar film and dried to obtain a positive electrode active layer green body.
[0044] (5) stacking the negative electrode current collector green sheet, the negative electrode active layer green sheet, the electrolyte separator green sheet and the positive electrode active layer green sheet, and statically pressing the whole to obtain a solid oxide electrolytic cell green sheet;
[0045] (6) The solid oxide electrolytic cell green body was heated to 730°C at a rate of 0.5°C / min, and kept at 180, 250, 350 and 730°C for 2 h respectively, and then heated to 1400°C at a rate of 1°C / min and kept at this temperature for 4 h to make the electrolyte diaphragm layer dense. After sintering, the body was cooled to 800°C at a rate of 3°C / min, and naturally cooled to room temperature in the furnace to obtain a solid oxide electrolytic cell with self-enrichment of carbon dioxide.
[0046] like Figures 1-2 The solid oxide electrolysis cell for self-enrichment of carbon dioxide obtained in this embodiment includes, from top to bottom: 20 μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -Zr 0.92 Y 0.16 O 2-δ Porosity of positive electrode active layer 4 is 20%; 10 μm Zr 0.92 Y 0.16 O 2-δ Electrolyte separator layer 3, 20 μm NiO-Zr 0.92 Y 0.16 O 2-δ Negative electrode active layer 2, porosity 20%; 400μm NiO-Zr 0.97 Y 0.06 O 2-δ The negative electrode current collecting layer 1 has a porosity of 45%.
[0047] Example 2
[0048] A method for preparing a solid oxide electrolytic cell for self-enrichment of carbon dioxide comprises the following steps:
[0049] (1) Preparation of negative electrode current collector green body: 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ 、Zr 0.97 Y 0.06 O 2-δ and graphite powder in a ratio of 51:34:15, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast and dried on a mylar film to obtain a negative electrode current collector green body.
[0050] (2) Preparation of negative electrode active layer green body: 0.8 Sr 0.2 )(Cr 0.5 Fe0.5 ) 3-δ 、Zr 0.92 Y 0.16 O 2-δ and graphite powder in a ratio of 54:36:10, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a mylar film and dried to obtain a negative electrode active layer green body.
[0051] (3) Preparation of electrolyte membrane green body: 0.92 Y 0.16 O 2-δ A two-component solvent of xylene and butyl acetate and an acrylic resin dispersant are added to the powder, a binder and a plasticizer are added after ball milling, and ball milling is performed again to obtain a uniformly dispersed casting slurry; the slurry is filtered and degassed, and then cast and dried on a Mylar film to obtain an electrolyte diaphragm green body.
[0052] (4) Preparation of positive electrode active layer green body: 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ 、Zr 0.92 Y 0.16 O 2-δ and graphite powder in a ratio of 54:36:10, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a mylar film and dried to obtain a positive electrode active layer green body.
[0053] (5) Preparation of positive electrode current collector green sheet: 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ 、Zr 0.97 Y 0.06 O 2-δ and graphite powder in a ratio of 51:34:15, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast and dried on a mylar film to obtain a positive electrode current collector green body.
[0054] (6) After stacking the negative electrode current collector green sheet, the negative electrode active layer green sheet, the electrolyte separator layer green sheet, the positive electrode active layer green sheet and the positive electrode current collector green sheet, the whole is statically pressed to obtain a solid oxide electrolytic cell green sheet.
[0055] (7) The solid oxide electrolytic cell green body was heated to 730°C at a rate of 0.5°C / min, and kept at 180, 250, 350 and 730°C for 2 h respectively, and then heated to 1400°C at a rate of 1°C / min and kept at this temperature for 4 h to make the electrolyte diaphragm layer dense. After sintering, the green body was cooled to 800°C at a rate of 3°C / min, and naturally cooled to room temperature in the furnace to obtain a solid oxide electrolytic cell with self-enrichment of carbon dioxide.
[0056] like Figures 3-4 The solid oxide electrolysis cell for self-enrichment of carbon dioxide obtained in this embodiment includes, from top to bottom: 200 μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -Zr 0.97 Y 0.06 O 2-δ Positive electrode current collecting layer 5, porosity 30%; 5μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -Zr 0.92 Y 0.16 O 2-δ Porosity of positive electrode active layer 4 is 20%; 5 μm Zr 0.92 Y 0.16 O 2-δ Electrolyte separator layer 3,5 μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -Zr 0.92 Y 0.16 O 2-δ Negative electrode active layer 2, porosity 20%; 200 μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -Zr 0.97 Y 0.06 O 2-δ The negative electrode current collecting layer 1 has a porosity of 30%.
[0057] Example 3
[0058] A method for preparing a solid oxide electrolytic cell for self-enrichment of carbon dioxide comprises the following steps:
[0059] 1) Preparation of negative electrode current collector green body:0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ 、Zr 0.97 Y 0.06 O 2-δ and graphite powder in a ratio of 51:34:15, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast and dried on a mylar film to obtain a negative electrode current collector green body.
[0060] (2) Preparation of negative electrode active layer green body: 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ ,La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 2.85 and graphite powder in a ratio of 54:36:10, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a mylar film and dried to obtain a negative electrode active layer green body.
[0061] (3) Preparation of electrolyte membrane green body: 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 2.85 A two-component solvent of xylene and butyl acetate and an acrylic resin dispersant are added to the powder, a binder and a plasticizer are added after ball milling, and ball milling is performed again to obtain a uniformly dispersed casting slurry; the slurry is filtered and degassed, and then cast and dried on a Mylar film to obtain an electrolyte diaphragm green body.
[0062] (4) Preparation of positive electrode active layer green body: 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ ,La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 2.85and graphite powder in a ratio of 54:36:10, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a mylar film and dried to obtain a positive electrode active layer green body.
[0063] (5) Preparation of positive electrode current collector green sheet: 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ 、Zr 0.97 Y 0.06 O 2-δ and graphite powder in a ratio of 51:34:15, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast and dried on a mylar film to obtain a positive electrode current collector green body.
[0064] (6) After stacking the negative electrode current collector green sheet, the negative electrode active layer green sheet, the electrolyte separator layer green sheet, the positive electrode active layer green sheet and the positive electrode current collector green sheet, the whole is statically pressed to obtain a solid oxide electrolytic cell green sheet.
[0065] (7) The solid oxide electrolytic cell green body was heated to 730°C at a rate of 0.5°C / min, and kept at 180, 250, 350 and 730°C for 2 h respectively, and then heated to 1400°C at a rate of 1°C / min and kept at this temperature for 4 h to make the electrolyte diaphragm layer dense. After sintering, the green body was cooled to 800°C at a rate of 3°C / min, and naturally cooled to room temperature in the furnace to obtain a solid oxide electrolytic cell with self-enrichment of carbon dioxide.
[0066] The solid oxide electrolysis cell for self-enrichment of carbon dioxide obtained in this example includes, from top to bottom: 50 μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -Zr 0.97 Y 0.06 O 2-δ Positive electrode current collecting layer 5, porosity 30%; 5μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 2.85Porosity of positive electrode active layer 4 is 20%; La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 2.85 Electrolyte separator layer 3,5 μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 2.85 Negative electrode active layer 2, porosity 20%; 50μm (La 0.8 Sr 0.2 )(Cr 0.5 Fe 0.5 ) 3-δ -Zr 0.97 Y 0.06 O 2-δ The negative electrode current collecting layer 1 has a porosity of 30%.
[0067] Example 4
[0068] A method for preparing a solid oxide electrolytic cell for self-enrichment of carbon dioxide comprises the following steps:
[0069] (1) Preparation of negative electrode current collector green body: 430L, Zr 0.97 Y 0.06 O 2-δ and graphite powder in a ratio of 48:32:20, then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a Mylar film and dried to obtain a green body of the negative electrode current collector layer;
[0070] (2) The steps of preparing the green body of the negative electrode active layer include: mixing 430L, Zr 0.92 Y 0.16 O 2-δ and graphite powder in a ratio of 51:34:15, and then add xylene and butyl acetate two-component solvent and acrylic resin dispersant, add binder and plasticizer after ball milling, and ball mill again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a mylar film and dried to obtain a negative electrode active layer green body.
[0071] (3) Preparation of electrolyte membrane green body: 0.92 Y 0.16 O 2-δA two-component solvent of xylene and butyl acetate and an acrylic resin dispersant are added to the powder, a binder and a plasticizer are added after ball milling, and ball milling is performed again to obtain a uniformly dispersed casting slurry; the slurry is filtered and degassed, and then cast and dried on a Mylar film to obtain an electrolyte diaphragm green body.
[0072] (4) Preparation of positive electrode active layer green body: 430L, Zr 0.92 Y 0.16 O 2-δ The graphite powder is mixed in a ratio of 51:35:15, and then a two-component solvent of xylene and butyl acetate and an acrylic resin dispersant are added. After ball milling, a binder and a plasticizer are added, and the ball milling is repeated to obtain a uniformly dispersed casting slurry. After filtering and degassing, the slurry is cast and dried on a Mylar film to obtain a green sheet of the positive electrode active layer.
[0073] (5) Preparation of positive electrode current collector green body: 430L, Zr 0.97 Y 0.06 O 2-δ and graphite powder in a ratio of 48:32:20, and then adding xylene and butyl acetate two-component solvent and acrylic resin dispersant, adding binder and plasticizer after ball milling, and ball milling again to obtain uniformly dispersed casting slurry; after filtering and degassing, the slurry is cast on a Mylar film and dried to obtain a positive electrode current collector green body;
[0074] (6) stacking the green sheets of the negative electrode current collector layer, the negative electrode active layer, the electrolyte separator layer, the positive electrode active layer, and the positive electrode current collector layer in a manner of static pressing the whole to obtain a green sheet of a solid oxide electrolytic cell;
[0075] (7) The solid oxide electrolytic cell green body was heated to 730°C at a rate of 0.5°C / min in a 4% H2-96% N2 atmosphere, and kept at 180, 250, 350 and 730°C for 2 h respectively. Then, the temperature was increased to 1400°C at a rate of 1°C / min and kept at this temperature for 4 h to make the electrolyte diaphragm layer dense. After sintering, the temperature was decreased to 800°C at a rate of 3°C / min, and naturally cooled to room temperature in the furnace to obtain a solid oxide electrolytic cell skeleton.
[0076] (8) According to NiO-Ce 0.9 G 0.1 O 2-δ Ni(NO3)2·6H2O, Ce(NO3)3·6H2O and Gd(NO3)3·6H2O were dissolved in deionized water in a stoichiometric ratio, citric acid was added in a ratio of 1:1 between citric acid and total cations, and the mixture was concentrated by heating at 80°C to obtain NiO-Ce with a total cation concentration of 1 mol / L. 0.9 G 0.1 O 2-δPrecursor solution, NiO-Ce 0.9 G 0.1 O 2-δ The precursor solution was impregnated into the negative electrode active layer 2 and the negative electrode current collecting layer 1, and calcined at 850°C in air for 2 h. The impregnation-calcination steps were repeated to make NiO-Ce 0.9 G 0.1 O 2-δ The catalyst loading is about 10 wt % relative to the positive electrode skeleton.
[0077] (9) According to Ce 0.9 G 0.1 O 2-δ Ce(NO3)3·6H2O and Gd(NO3)3·6H2O were dissolved in deionized water in a stoichiometric ratio, citric acid was added in a ratio of 1:1 between citric acid and total cations, and the mixture was heated and concentrated at 80°C to obtain Ce with a total cation concentration of 1 mol / L. 0.9 G 0.1 O 2-δ Precursor solution, Ce 0.9 G 0.1 O 2-δ The precursor solution was impregnated into the positive electrode active layer 4 and the positive electrode current collecting layer 5, and calcined at 850°C in air for 2 h. The impregnation-calcination steps were repeated to make Ce 0.9 G 0.1 O 2-δ The catalyst loading is about 10 wt.% relative to the positive electrode skeleton.
[0078] The solid oxide electrolytic cell for self-enrichment of carbon dioxide obtained in this embodiment includes, from top to bottom, a 200 μm 430L positive electrode current collector layer 5 with a porosity of 45%; a 5 μm 430L-Zr 0.92 Y 0.16 O 2-δ Porosity of positive electrode active layer 4 is 35%; 5μm Zr 0.92 Y 0.16 O 2-δ Electrolyte separator layer 3, 5 μm 430L-Zr 0.92 Y 0.16 O 2-δ The negative electrode active layer 2 has a porosity of 35%; the 200μm 430L negative electrode current collector layer 1 has a porosity of 45%. 0.92 Y 0.16 O 2-δ Ce is loaded in the positive electrode active layer 4 0.9 G 0.1 O 2-δThe nano catalyst has an average particle size of 1 to 500 nm and a loading amount of 10 wt.% of the positive electrode skeleton. In the porous 430L negative electrode current collector 1 and 430L-Zr 0.92 Y 0.16 O 2-δ The negative electrode active layer 2 is loaded with NiO-Ce 0.9 G 0.1 O 2-δ The nano catalyst has an average particle size of 1 to 500 nm and a loading amount of 10 wt.% of the negative electrode skeleton.
[0079] Example 5
[0080] The solid oxide electrolytic cell of Example 1 was used and sealed in a test fixture, as shown in FIG. Figure 5 The test fixture was divided into a positive electrode chamber and a negative electrode chamber by the solid oxide electrolytic cell. 80% H2O-20% H2 (560ml / min H2O-140ml / min H2) was introduced into the negative electrode chamber, and 105ml / min CH4 was introduced into the positive electrode chamber, and the temperature was raised to 700°C. Figure 6 As the electrolysis current increases, the water vapor in the negative electrode chamber is gradually electrolyzed to produce hydrogen and oxygen ions, and the natural gas in the positive electrode chamber is oxidized by oxygen ions to produce CO2 and H2O. When the electrolysis current increases to 60A, the CH4 in the positive electrode chamber is completely oxidized to CO2 and H2O, and the tail gas in the negative electrode chamber is 80% H2-20% H2O (560ml / min H2-140ml / min H2O). At this time, the electrolysis power consumption is 0.87kwh per standard cubic meter of hydrogen. Figure 7 The tail gas in the positive electrode chamber is condensed to obtain pure CO2, and the tail gas in the negative electrode chamber is condensed to obtain pure H2.
[0081] Example 6
[0082] The solid oxide electrolytic cell in Example 2 was used and sealed in a test fixture. The test fixture was divided into a positive electrode chamber and a negative electrode chamber by the solid oxide electrolytic cell. 80% H2O-20% H2 (560 ml / min H2O-140 ml / min) was introduced into the negative electrode chamber. H2), 255ml / min coke oven gas (composition of 60% H2, 25% CH4, 3% CO2, 5% CO, 5% H2O, 2% N2) is introduced into the positive electrode chamber, and the temperature is raised to 700°C. As the electrolysis current increases, the water vapor in the negative electrode chamber is gradually electrolyzed to produce hydrogen and oxygen ions, and the coke oven gas in the positive electrode chamber is oxidized by oxygen ions to produce CO2 and H2O. When the electrolysis current increases to 60A, the coke oven gas in the positive electrode chamber is completely oxidized to CO2 and H2O. The tail gas in the positive electrode chamber is 76.67% H2O-22% CO2-1.33% N2 (293.25ml / min H2O-91.8ml / min CO2-5.1ml / min N2), and the tail gas in the negative electrode chamber is 80% H2-20% H2O (560ml / min H2-140ml / min H2O); the tail gas in the positive electrode chamber is condensed to obtain 94.7% CO2-5.3% N2, and the tail gas in the negative electrode chamber is condensed to obtain pure H2.
[0083] Example 7
[0084] This example aims to explore the relationship between the thickness and porosity of each layer and the electrolysis and hydrogen production performance of a solid oxide electrolysis cell for self-enrichment of carbon dioxide.
[0085] The remaining preparation steps are the same as those in Example 4, except that the porosity of the negative electrode current collector layer 1 is set to 10%, 20%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, respectively, the thickness of the negative electrode current collector layer 1 is set to 50 μm, 100 μm, 500 μm, 1000 μm, 1500 μm, 2000 μm, respectively, the porosity of the negative electrode active layer 2 is set to 20%, 25%, 30%, 35%, respectively, the thickness of the negative electrode active layer 2 is set to 5 μm, 10 μm, 15 μm, 20 μm, respectively, and the thickness of the electrolyte 3 is set to 100 μm, 100 μm, 150 μm, 200 μm, respectively. The porosity of the positive electrode active layer 4 is set to 20%, 25%, 30%, 35%, the thickness of the positive electrode active layer 4 is set to 5μm, 10μm, 15μm, 20μm, the porosity of the positive electrode collecting layer 5 is set to 10%, 20%, 30%, 35%, 40%, 45%, 50%, 60%, 70%, and the thickness of the positive electrode collecting layer 5 is set to 50μm, 100μm, 500μm, 1000μm, 1500μm, 2000μm. The electrolytic hydrogen production test was conducted, and the results showed that: the best electrolytic hydrogen production performance was achieved when the porosity of the negative electrode active layer 2 was between 20% and 35%, the best electrolytic hydrogen production performance was achieved when the thickness of the negative electrode active layer 2 was between 5 and 20 μm, the best electrolytic hydrogen production performance was achieved when the porosity of the positive electrode active layer 4 was between 20% and 35%, the best electrolytic hydrogen production performance was achieved when the thickness of the positive electrode active layer 2 was between 5 and 20 μm, and the best electrolytic hydrogen production performance was achieved when the porosity of the negative electrode current collector layer 1 was between 45% and 50%. Below this porosity, the conversion rate of water vapor is low, resulting in poor electrolytic hydrogen production performance. The performance is poor, and the electrolytic hydrogen production performance is good when the porosity is higher than this porosity. The porosity of the positive electrode current collecting layer 5 is between 45% and 50%, which has the best electrolytic hydrogen production performance. Below this porosity, the conversion rate of water vapor is low, resulting in poor electrolytic hydrogen production performance. Above this porosity, the electrolytic hydrogen production performance is good. When the total thickness of the solid oxide electrolytic cell is less than 300μm, the electrolytic hydrogen production performance cannot be measured due to the failure of the electrolytic cell. The thickness of the electrolyte 3 has better electrolytic hydrogen production performance between 5-300μm. Above 300μm, the electrolytic hydrogen production performance will be poor due to the large ohmic resistance, as shown in Table 1.
[0086] Table 1 Hydrogen production performance of solid oxide electrolysis cells with different layer thickness and porosity
[0087]
[0088] Comparative Example 1
[0089] The remaining steps of this comparative example are the same as those of Example 4, except that 430L in the positive electrode active layer 4 and the positive electrode current collecting layer 5 is replaced by Ni. The electrolysis hydrogen production test was conducted, and it was found that carbon deposition in the pores of the positive electrode active layer 4 and the positive electrode current collecting layer 5 rapidly caused the electrolysis cell to fail, and the electrolysis voltage increased rapidly when the hydrocarbon fuel conversion rate was higher than 80%.
[0090] Among the above embodiments, the best embodiment is Embodiment 4.
Claims
1. A solid oxide electrolysis cell for self-enrichment of carbon dioxide, characterized in that: The invention comprises a negative electrode current collecting layer (1), wherein a negative electrode active layer (2), an electrolyte membrane (3), and a positive electrode active layer (4) are sequentially arranged on the surface of the negative electrode current collecting layer (1); the negative electrode current collecting layer (1) is one or more of an electronic conductive phase and an ion conductive phase; the negative electrode active layer (2) and the positive electrode active layer (4) are composite ceramics composed of an electronic conductive phase and an ion conductive phase, and the volume fraction of the electronic conductive phase is not less than 40%; the porosity of the negative electrode current collecting layer (1) is 10-70%, the porosity of the negative electrode active layer (2) is 20-35%, and the porosity of the positive electrode active layer (4) is 20-35%.
2. A solid oxide electrolysis cell for self-enrichment of carbon dioxide according to claim 1, characterized in that: The electronic conductive phases in the negative electrode current collecting layer (1) and the negative electrode active layer (2) are Ni, Fe, Cu, Co, FeNi3, 430L, SUS445, SUS446, NiO, CuO, Fe3O4, Co3O4, (La 1-x Sr x )(Cr 1-y Fe y ) 3-δ , (La 1-x Sr x )(Cr 1-y Mn y ) 3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y-z Ni y Mo z O 6-δ One or more of the following, wherein 0<x<1, 0<y<1, 0<δ<1; the ion conductive phase in the negative electrode current collecting layer (1) and the negative electrode active layer (2) is one or more of doped zirconium oxide, doped cerium oxide, doped lanthanum gallate, doped barium zirconate, and doped barium ceria.
3. A solid oxide electrolysis cell for self-enrichment of carbon dioxide according to claim 1, characterized in that: The electronic conductive phase in the positive electrode active layer (4) is 430L, SUS445, SUS446, (La 1-x Sr x )(Cr 1-y Fe y ) 3-δ , (La 1- x Sr x )(Cr 1-y Mn y ) 3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y-z Ni y Mo z O 6-δ One or more of the following, wherein 0<x<1, 0<y<1, 0<δ<1; the ion conductive phase in the positive electrode active layer (4) is one or more of doped zirconium oxide, doped cerium oxide, doped lanthanum gallate, doped barium zirconate, and doped barium ceria.
4. A solid oxide electrolysis cell for self-enrichment of carbon dioxide according to claim 1, characterized in that: The inner surfaces of the negative electrode current collecting layer (1), the negative electrode active layer (2) and the positive electrode active layer (4) are all covered with nano-negative electrode catalysts with a particle size of 1 to 500 nm. The nano-negative electrode catalysts are Fe, Ni, Cu, Co, FeNi3, Ce, 1-x La x O 2-δ 、Ce 1-x Y x O 2-δ 、Ce 1- x Sm x O 2-δ 、Ce 1-x G x O 2-δ 、Ce 1-x Pr x O 2-δ 、Ce 1-x Nd x O 2-δ 、Ce 1-x Ca x O 2-δ 、Ce 1-x Mg x O 2-δ , (La 1-x Sr x )(Cr 1- y Fe y ) 3-δ , (La 1-x Sr x )(Cr 1-y Mn y ) 3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y-z Ni y Mo z O 6-δ One or more of , wherein 0<x<1, 0<δ<1.
5. A solid oxide electrolysis cell for self-enriching carbon dioxide according to any one of claims 1 to 4, characterized in that: A positive electrode current collecting layer (5) is also arranged on the surface of the positive electrode active layer (4), and the positive electrode current collecting layer (5) is one or more of an electronic conductive phase and an ion conductive phase.
6. A solid oxide electrolysis cell for self-enrichment of carbon dioxide according to claim 5, characterized in that: The electronic conductive phase in the positive electrode current collecting layer (5) is 430L, SUS445, SUS446, (La 1-x Sr x )(Cr 1-y Fe y ) 3-δ , (La 1- x Sr x )(Cr 1-y Mn y ) 3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y-z Ni y Mo z O 6-δ One or more of the following, 0<x<1, 0<y<1, 0<δ<1.
7. A solid oxide electrolysis cell for self-enrichment of carbon dioxide according to claim 5, characterized in that: The ion conductive phase in the positive electrode current collecting layer (5) is one or more of doped zirconium oxide, doped cerium oxide, doped lanthanum gallate, doped barium zirconate, and doped barium ceria, and has a porosity of 10 to 70%.
8. A solid oxide electrolysis cell for self-enrichment of carbon dioxide according to claim 5, characterized in that: The inner surfaces of the positive electrode current collecting layer (5) and the positive electrode active layer (4) are covered with nano positive electrode catalysts with a particle size of 1 to 500 nm. The nano positive electrode catalysts are Fe, Ni, Cu, Co, FeNi3, Ce, 1-x La x O 2-δ 、Ce 1-x Y x O 2-δ 、Ce 1-x Sm x O 2-δ 、Ce 1-x G x O 2-δ 、Ce 1- x Pr x O 2-δ 、Ce 1-x Nd x O 2-δ 、Ce 1-x Ca x O 2-δ 、Ce 1-x Mg x O 2-δ , (La 1-x Sr x )(Cr 1-y Fe y ) 3-δ , (La 1-x Sr x )(Cr 1- y Mn y ) 3-δ , (La 1-x Sr x )TiO 3-δ ,La 2-x Sr x Fe 2-y-z Ni y Mo z O 6-δ One or more of , wherein 0<x<1, 0<δ<1.
9. A solid oxide electrolysis cell for self-enrichment of carbon dioxide according to claim 1 or 2, characterized in that: The thickness of the negative electrode current collecting layer (1) is 50 to 2000 mm, the thickness of the negative electrode active layer (2) is 5 to 20 microns, the thickness of the electrolyte membrane (3) is 1 to 1000 microns, the thickness of the positive electrode active layer (4) is 50 to 2000 microns, the thickness of the positive electrode current collecting layer (5) is 50 to 2000 microns, and the total thickness of the solid oxide electrolytic cell for self-enriching carbon dioxide is not less than 300 microns.
10. The method for preparing a solid oxide electrolytic cell for self-enrichment of carbon dioxide according to claim 1, characterized in that: The following steps are involved: Step 1, preparing a negative electrode current collecting layer green body, a negative electrode active layer green body, an electrolyte separator green body, a positive electrode active layer green body and a positive electrode current collecting layer green body on a Mylar film respectively; Step 2, stacking the negative electrode current collector green sheet, the negative electrode active layer green sheet, the electrolyte separator green sheet, the positive electrode active layer green sheet and the positive electrode current collector green sheet, and statically pressing the whole to obtain a solid oxide electrolytic cell green sheet; Step three, gradient sintering the product obtained in step two to make the electrolyte membrane layer dense, cooling, and obtaining a solid oxide electrolysis cell that self-enriches carbon dioxide.
Citation Information
Patent Citations
Method and apparatus for producing hydrogen
CN101103140A
Natural gas-assisted steam electrolyzer
US6051125A
Proton conductor solid oxide battery with negative electrode barrier layer
CN114628753A
Current collector and preparation method thereof
CN114824302A
Electrode, solid -state oxide fuel cell and solid -state oxidation thing electrolytic bath
CN207459069U